To study gamma-glutamyl transferase levels in heart failure - Fida Hussain Mitha Bhai; Sangram Biradar (Wolters Kluwer Medknow Publications, 2020)
Background and Aims: Serum gamma-glutamyl transferase (Sr.GGT) is associated with incident cardiovascular diseases and is a potential risk factor for disease mortality. We investigated the relevance of circulating Sr.GGT levels in heart failure (HF) patients. Materials and Methods: About 50 patients admitted with diagnosed HF according to Framingham's clinical criteria, irrespective of etiology, and type of HF were enrolled in the study and their baseline Sr.GGT levels were estimated. They were grouped into ischemic and nonischemic (valvular) cause of HF. Type of HF was based on the ejection fraction (EF%) on echocardiography reduced the EF (<40%), mid-range or preserved EF >40%). Statistical analysis was presented as frequency (percentage) and continuous as mean ± standard deviation. Inferential statistics such as Chi-square test/Fischer's exact test was used. Results: The mean age of the study patients was 58.20 ± 14.98 years. Both genders were homogeneously spread across the different age groups in the study. It was found that Sr.GGT levels were best correlated in the age groups below 65 years. Significant association was seen when patients were studied by stratifying them gender wise, divided into quartiles. Valvular heart disease and its association with Sr.GGT levels were found to be statistically significant (P = 0.001). Whereas no association was found in the given sample between coronary artery disease/ischemic heart disease and Sr.GGT levels. Significant association in patients with comorbid conditions was found, indicative that comorbidities contributed as a confounding factor in the study.Conclusion: This study is limited by its observational nature; it does not permit conclusions on causal relationships. Sr.GGT levels done at baseline in patients with HF may not be helpful to prognosticate HF. Serial follow-up studies in a larger sample size are required.